Fresh aboveground net primary productivity of Tibetan grasslands: Responses of different plant functional groups to climate change and human activities and implications for ecosystem management - Guangyu Zhang; Wei Sun; Shaowei Li; Zhiming Zhong; Yuan Tian; Chenjun Zhao; Fusong Han; Shaolin Huang; Dunzhu Yujie; Gang Fu (PLoS ONE, 2026)
Uncertainties remain regarding how climate change and human activities affect the aboveground net primary productivity (ANPP) of grassland ecosystems, particularly the differential responses of distinct plant functional groups. Here, we investigate the alpine grasslands of the Qinghai-Xizang Plateau from 2000 to 2022, focusing on the fresh ANPP of the whole plant community and three key functional groups (sedges, graminoids, and forbs). Our objectives are to identify the spatiotemporal trends of ANPP and to determine the dominant drivers (climate vs. human activities) of these changes. Under the combined effects of climate change and human activities, the spatially averaged relative changes in fresh ANPP were –1.15% for the whole community, + 5.67% for sedges, –1.55% for graminoids, and –2.26% for forbs. Regional patterns varied, with some areas showing increasing or decreasing trends over time, while others exhibited no significant change. Climate change dominated 20.79% of the grassland area, human activities dominated 54.26%, and the two drivers jointly dominated 24.95%. When the ANPP of the three functional groups were considered together, the area where all three groups jointly regulated grassland fresh ANPP accounted for the largest proportion (39.12%), followed by areas dominated by forbs (35.43%), sedges (18.27%), and graminoids (7.18%). These results reveal pronounced geographical heterogeneity in the trends of fresh ANPP, both for the whole community and for individual functional groups. Human activities exert a larger controlling influence than climate change over the observed ANPP changes. Moreover, the contribution of each functional group to community ANPP varies spatially. Our findings provide a scientific basis for understanding grassland ecosystem functioning and for developing targeted conservation and management strategies.